2003
DOI: 10.1073/pnas.1434381100
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide regulates K + and Cl - channels in guard cells through a subset of abscisic acid-evoked signaling pathways

Abstract: Abscisic acid (ABA) triggers a complex sequence of signaling events that lead to concerted modulation of ion channels at the plasma membrane of guard cells and solute efflux to drive stomatal closure in plant leaves. Recent work has indicated that nitric oxide (NO) and its synthesis are a prerequisite for ABA signal transduction in Arabidopsis and Vicia guard cells. Its mechanism(s) of action is not well defined in guard cells and, generally, in higher plants. Here we show directly that NO selectively regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
245
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 363 publications
(276 citation statements)
references
References 46 publications
12
245
0
5
Order By: Relevance
“…Consequently, NO activates signalling pathways, which results in changes of gene expression, through intermediate cellular messengers. Several lines of evidence indicate that cGMP acts downstream of NO signalling (Durner, Wendehenne & Klessig 1998;García-Mata et al 2003;Neill, Desikan & Hancock 2003;Pagnussat, Lanteri & Lamattina 2003). Interestingly, it was recently reported that cGMP is required for the NO-dependent expression of genes involved in the flavonoid biosynthetic pathway (Suita et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, NO activates signalling pathways, which results in changes of gene expression, through intermediate cellular messengers. Several lines of evidence indicate that cGMP acts downstream of NO signalling (Durner, Wendehenne & Klessig 1998;García-Mata et al 2003;Neill, Desikan & Hancock 2003;Pagnussat, Lanteri & Lamattina 2003). Interestingly, it was recently reported that cGMP is required for the NO-dependent expression of genes involved in the flavonoid biosynthetic pathway (Suita et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Production of ROS such as hydrogen peroxide (H 2 O 2 ) and the reactive nitrogen species nitric oxide (NO) in response to ABA are recently discovered signaling mechanisms in guard cells [73][74][75][76]. Pharmacological manipulations coupled with mutant analysis of both ROS and NO pathways indicate that ABA-induced H 2 O 2 production stimulates NO production and NO is required for H 2 O 2 induced-stomatal closure.…”
Section: K + Channels: Properties and Regulationmentioning
confidence: 99%
“…NO-stimulated intracellular Ca 2+ -release inhibits inward K + currents in a phosphorylation-dependent manner. Broad range protein kinase inhibitors inhibit intracellular Ca 2+ release and render inward K + currents insensitive to pharmacologically produced NO [74], suggesting that NO-induced Ca 2+ release is kinasedependent, and that the NO effect on inward K + channels is due to Ca 2+ -based inhibition [78]. Thus, the overall signaling cascade appears to be a pathway from ABA to ROS production to NO production to alteration in protein phosphorylation status to endomembrane Ca 2+ release to K þ in channel inhibition; however, additional parallel pathways may exist.…”
Section: K + Channels: Properties and Regulationmentioning
confidence: 99%
“…When [Ca 2+ ] cyt elevation in guard cells was blocked by LaCl 3 , SO 2 toxicity was blocked. Furthermore, suppression of the elevation of NO (Pei et al 2000;Lamotte et al 2006); meanwhile, NO also selectively activates intracellular Ca 2+ channels via a cGMPdependent pathway in V. faba guard cells (Garcia-Mata et al 2003). Intracellular Ca 2+ increases were reported to be a consequence of an uptake from the extracellular space or due to Ca 2+ liberation from intracellular stores.…”
Section: Discussionmentioning
confidence: 99%